Word Guessing Game Learning Media Norm Material Improves Student Learning Outcomes - Ardani, Maryami Balqis; Susilo Tri Widodo (LPPM Undiksha, 2024)
The media used is less effective in learning activities and influences learning outcomes. Based on this, this research aims to develop a learning media platform, Word Guessing Game Learning Media, which can improve the learning outcomes of fifth-grade elementary school students. This research is development research. The model used to develop media is ADDIE. The subject of this research involved 1 (one) learning content/material expert 1 (one) learning media expert. The test subjects for this research were divided into 2 groups: a small group of 6 students and a large group of 26 students. The methods used to collect data are observation, interviews, questionnaires, and tests. Data collection instruments are questionnaire sheets and tests. The techniques used to analyze data are qualitative and quantitative descriptive analysis, and N-gain is used to test the effectiveness of learning media. The research results show that product quality is included in the very appropriate criteria, with a score obtained from media experts of 88.5 and material experts of 92.5. The media developed meets practical criteria by obtaining an average score on the student response questionnaire with a percentage of 100%. The media meets the criteria of being quite decent, with an average score obtained from student post-test results of 85 with a completion percentage of 100%. It was concluded that the Word Guessing Game learning media could improve the learning outcomes of fifth-grade elementary school students.